2019
DOI: 10.3390/ijms20122935
|View full text |Cite
|
Sign up to set email alerts
|

Protein Engineering of Dual-Cys Cyanobacteriochrome AM1_1186g2 for Biliverdin Incorporation and Far-Red/Blue Reversible Photoconversion

Abstract: Cyanobacteria have cyanobacteriochromes (CBCRs), which are photoreceptors that bind to a linear tetrapyrrole chromophore and sense UV-to-visible light. A recent study revealed that the dual-Cys CBCR AM1_1186g2 covalently attaches to phycocyanobilin and exhibits unique photoconversion between a Pr form (red-absorbing dark state, λmax = 641 nm) and Pb form (blue-absorbing photoproduct, λmax = 416 nm). This wavelength separation is larger than those of the other CBCRs, which is advantageous for optical tools. Now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…Anacy_2551g3 from Anabaena cylindrica PCC7122 is so far the protein with the longest absorption among CBCRs that also shows a most red-shifted fluorescence with λ max = 728 nm and λ em = 740 nm; its fluorescence quantum yield Φ fl = 1.2% is moderate, but this protein might serve as a “lead structure” initiating further improvements reminiscent to bPhys . Other potentially relevant candidates for applications might be proteins such as the dual-Cys CBCR Am1186g2 from Acaryochloris marina that has been converted to bind BV as chromophore . A detailed analysis on this representative for an entire lineage revealed that proteins from this group bind BV or its 18′,18″-derivative, keeping an eye on the possibility that these chromophores might allow an extension of the absorption further into the red range of the spectrum .…”
Section: Bilin-binding Red-light-sensitive Photoreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anacy_2551g3 from Anabaena cylindrica PCC7122 is so far the protein with the longest absorption among CBCRs that also shows a most red-shifted fluorescence with λ max = 728 nm and λ em = 740 nm; its fluorescence quantum yield Φ fl = 1.2% is moderate, but this protein might serve as a “lead structure” initiating further improvements reminiscent to bPhys . Other potentially relevant candidates for applications might be proteins such as the dual-Cys CBCR Am1186g2 from Acaryochloris marina that has been converted to bind BV as chromophore . A detailed analysis on this representative for an entire lineage revealed that proteins from this group bind BV or its 18′,18″-derivative, keeping an eye on the possibility that these chromophores might allow an extension of the absorption further into the red range of the spectrum .…”
Section: Bilin-binding Red-light-sensitive Photoreceptorsmentioning
confidence: 99%
“…69 Other potentially relevant candidates for applications might be proteins such as the dual-Cys CBCR Am1186g2 from Acaryochloris marina that has been converted to bind BV as chromophore. 70 A detailed analysis on this representative for an entire lineage revealed that proteins from this group bind BV or its 18′,18″-derivative, keeping an eye on the possibility that these chromophores might allow an extension of the absorption further into the red range of the spectrum. 18 It is important to note that in all cases of chemical modification of those bilins that serve as chromophores, the double bond prone to light-induced isomerization (between rings C and D) remains intact (Figures 1 and 5).…”
Section: Introductionmentioning
confidence: 99%
“…In this Thematic Area, 56 articles have been published [ 48 , 64 , 104 , 108 , 110 , 124 , 195 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 ], an...…”
Section: Articles On the Various Directionsunclassified
“…A more detailed examination shows that, in this direction, as well as in the previous ones, articles in which the objects of research are organic materials clearly prevail over articles in which the objects of research are inorganic materials (36 and 20, respectively). Wherein, the overwhelming majority of articles of the “organic” profile are, in one way or another, connected with the participation of the objects with a biological origin; these include [ 64 , 124 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 274 , 277 , 278 , 282 , 284 , 289 , 291 , 292 , 293 , 294 , 295 , 296 , 298 , 299 , 300 ] and the processes in abiogenic organic materials were considered only in [ 48 , 195 , 266 , 271 , 272 , 273 , 283 , 288 , 290 ]. The thematic focus of these works, as well as the chemical compounds studied in them, is also very diverse, and even a simple listing of them here is clearly beyond the scope of this article, too.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%
“…CBCR receptors are spectrally tuned via binding pocket chemistry changes, which can take a variety of different forms. ,,, As an example, AnPixJ, a homologue of TePixJ, also from Thermosynechococcus elongatus, binds phycocyanobilin instead of phycoviolobilin and has very similar chromophore orientations to TePixJ in the Pg state, but instead of converting to a blue light-absorbing state when excited as TePixJ does, it becomes red-absorbing with a similar chromophore structure to the Cph1 photoreceptor’s red-absorbing state. , This spectral tuning and the relatively small size of these photoreceptors make them attractive targets for optogenetic tool development. …”
Section: Introductionmentioning
confidence: 99%